2021
DOI: 10.3390/su13095006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Autonomy Support Intervention on the Involvement of Higher Education Students

Abstract: Intervention studies based on Self-Determination Theory (SDT) in educational contexts prove the importance of the teacher’s motivating interpersonal style, promoting positive results in students’ motivation. However, college practices and processes have new challenges. This study examines the repercussions of an intervention program with autonomy support on students’ involvement. The sample was randomly divided into two groups, an intervention group composed of 12 teachers, aged between 25 and 56 years (M = 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…This has resulted in significant differences between learners in the two groups, which could be due to the lack of intervention in the control group where no significant changes in learner autonomy were observed. The improvements in student autonomy variables due to intervention in EFL classes in this study replicate those revealed by interventions in other disciplines (e.g., Lozano-Jiménez et al, 2021).…”
Section: Post-test Findingssupporting
confidence: 77%
See 3 more Smart Citations
“…This has resulted in significant differences between learners in the two groups, which could be due to the lack of intervention in the control group where no significant changes in learner autonomy were observed. The improvements in student autonomy variables due to intervention in EFL classes in this study replicate those revealed by interventions in other disciplines (e.g., Lozano-Jiménez et al, 2021).…”
Section: Post-test Findingssupporting
confidence: 77%
“…These results empirically validate the theoretical assumptions about the practicality of autonomysupportive teaching in promoting EFL learner autonomy (e.g., Reeve, 2005Reeve, , 2009Benson, 2011;Dam, 2011;Ikonen, 2013;Sella, 2014;Pichugova et al, 2016;Hu and Zhang, 2017;Suharmoko, 2017;Gurbanov and Mirzayeva, 2018;Reeve et al, 2019;Yu, 2020;Saeed, 2021). They also verify the fact that pedagogical autonomy interventions in foreign language classroom setting are not only possible as theoretically hypothesized but also actually effective as is in other fields (e.g., Cheon et al, 2012;Lozano-Jiménez et al, 2021). Further, the study findings experimentally support the theoretical claims about the feasibility, desirability, and teachability of autonomy in classroom setting (see, e.g., Ellis and Sinclair, 1989;Ikonen, 2013;Raya et al, 2020;Reeve, 1998), and the applicability of this concept to be incorporated in L2 instruction across different EFL contexts even if it has not been a part of the educational background in that context like in Saudi Arabia.…”
Section: Causal Associationssupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, our findings support the fact that during the implementation of the CPCCs, PST motivation can be related to the teaching process of teachers providing basic psychological needs. As reported by Lozano-Jiménez et al [50], the effectiveness in the application of an educational approach not only depends on the perception of PST autonomy support to improve PST involvement but also by the improvement of the synergistic effects between the PST psychological needs and academic motivation. Indeed, in our experiments, there was a synergistic effect between the academic motivation by the PSTs during the implementation of the CPCCs in the schools.…”
Section: Synergistic Interplay Between Motivation and Need-supportive Teaching Dimensionsmentioning
confidence: 85%